2018
DOI: 10.18203/2394-6040.ijcmph20184817
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anemia among adolescent girls in a North Karnataka school: a cross sectional study

Abstract: Background: World Health Organization (WHO) has defined ‘Adolescence’ as a period between 10 and 19 years. Anemia is a condition characterized by reduction in the number of red blood cells and/or hemoglobin concentration. Adolescent girls are at increased risk of anemia due to rapid growth and developmental process. The objectives of the study were to estimate the prevalence of anemia among adolescent girls in one of the schools in North Karnataka.Methods: A cross sectional study was conducted among adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
3
3
0
1
Order By: Relevance
“…Most (74%) of adolescent girls had attained onset of menarche while 26% of adolescent girls had not attained onset of menarche. The findings are consistent with the findings of the study conducted by Toppo M, etal 8 where it was found that the most of girls (36.4%) belong to age group 14-16 years. Mostly (80%) of girls had attained menarche.…”
Section: Discussionsupporting
confidence: 93%
“…Most (74%) of adolescent girls had attained onset of menarche while 26% of adolescent girls had not attained onset of menarche. The findings are consistent with the findings of the study conducted by Toppo M, etal 8 where it was found that the most of girls (36.4%) belong to age group 14-16 years. Mostly (80%) of girls had attained menarche.…”
Section: Discussionsupporting
confidence: 93%
“…Various studies on prevalence of anaemia among adolescent girls reported prevalence ranging from 39% to 90% in different parts of India. [ 12 15 16 17 18 19 20 21 ] This vast range of prevalence of anaemia may be due to different methods of haemoglobin estimation, different study settings and different study periods. Few studies had adopted standard method for haemoglobin estimation, thus calling for a uniform prospective study of adolescent population using digital haemoglobinometer with high precision.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] in Udupi and Patil N et al . [ 17 ] in North Karnataka. This difference in findings may be due to different cut-off used to classify anaemia in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical signs, paleness of (eyes, lips, tongue, skin, nails, gums) reported among AG were statistically significant (p<0.005) to the prevalence of anaemia. Studies by some authors reported 28.12% of conjunctival pallor among adolescent girls [19], 16% pale skin and 5.7 % pigmentation of nails [18], 52.3% pallor of conjunctiva, tongue and nail bed [20] among the adolescent girls. Symptoms such as (breathlessness, giddiness, fatigue, loss of appetite, frequent headache, pica) was mostly observed in moderately anaemic followed by severely anaemic girls which is statistically significant.…”
Section: Discussionmentioning
confidence: 99%